Innovative Early Childhood STEM Education with ChatGPT: Teacher Perspectives - Ugras, Hilal; Ugras, Mustafa; Papadakis, Stamatios; Kalogiannakis, Michail (Springer, 2025)
This study aims to evaluate the integration of AI-supported ChatGPT into early childhood STEM education from the teachers' perspective. The study group comprised 18 teachers who had previously received training on the use of ChatGPT. A phenomenological approach was adopted within the qualitative research framework, utilising a semi-structured interview form and researcher diaries as data collection tools. The collected data were analysed using content analysis with the aid of MAXQDA software, and the findings were interpreted based on predefined categories and codes. The study's findings indicate that teachers generally agree that integrating ChatGPT into early childhood STEM education would be beneficial. Teachers highlighted the significant role of ChatGPT in providing instant feedback, including personalised content suggestions, encouraging creativity, enhancing real-life relevance, and boosting student motivation. Additionally, ChatGPT's features accelerated the educational process, offering teachers greater flexibility in planning and promoting equality among students. However, challenges in integrating ChatGPT were also identified, including technical issues, student-related difficulties, and a need for more security knowledge. To address these challenges, teachers should receive both technical and pedagogical support. In conclusion, while integrating ChatGPT into early childhood STEM education presents numerous advantages, it also requires careful management. Recommendations include providing pedagogical support for teachers, offering information literacy training for students, and implementing strategies to ensure a smooth integration process.
Keywords: ChatGPT; Early childhood STEM education; Artificial intelligence; AI; Innovative technology; Teacher views